PENGARUH PERSEPSI KEMUDAHAN KEUANGAN E-WALLET SHOPEPAY, PRESEPSI KEGUNAAN KEUANGAN E-WALLET SHOPEPAY DAN PROMOSI KEUANGAN E-WALLET SHOPEPAY TERHADAP PERILAKU KEUANGAN KONSUMTIF GENERASI Z DI YOGYAKARTA - Syahbilla Erza Prasiwi; Sulastiningsih Sulastiningsih (LPPM PoliteknikPratamaKendal- Universitas Sains Dan Teknologi Komputer, 2025)
This study aims to influence the perception of convenience, perception of usefulness and promotion on Shopeepay E-Wallet on generation z consumptive behavior in Yogyakarta. The research method uses a quantitative method by conducting multiple linear regression between perception of convenience, perception of usefulness and promotion on generation z consumptive behavior in Yogyakarta. The sample in this study was determined by purposive sampling. This study concludes that the variables of perception of convenience and perception of usefulness influence the consumptive behavior of generation z in Yogyakarta while the promotion variable does not influence the consumptive behavior of generation z in Yogyakarta. The R² value shows a value of 0.315. This identifies that all independent variables (perception of convenience, perception of usefulness and promotion) are able to influence the dependent variable (consumptive behavior) by 68.5%